Sensitive Quantitative Detection of Commensal Bacteria by rRNA-Targeted Reverse Transcription-PCR - Matsuda, Kazunori (American Society for Microbiology, 2007)
A sensitive rRNA-targeted reverse transcription-quantitative PCR (RT-qPCR) method was developed for exact and sensitive enumeration of subdominant bacterial populations. Using group- or species-specific primers for 16S or 23S rRNA, analytical curves were constructed for Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, Clostridium perfringens, and Pseudomonas aeruginosa, and the threshold cycle value was found to be linear up to an RNA amount of 10(−3) cell per RT-PCR. The number of bacteria in culture was determined by RT-qPCR, and the results correlated well with the CFU count over the range from 10(0) to 10(5) CFU. The bacterial counts obtained by RT-qPCR were the same as the CFU counts irrespective of the growth phase in vitro, except for C. perfringens during starvation periods; the viable cell counts obtained by using a combination of 4′,6-diamidino-2-phenylindole (DAPI) staining and SYTO9-propidium iodide double staining were in good agreement with the RT-qPCR counts rather than with the CFU counts. The RT-qPCR method could detect endogenous Enterobacteriaceae and P. aeruginosa in feces of hospitalized patients (n = 38) at a level of 10(3) cells per g of feces, and for enumeration of S. aureus or P. aeruginosa spiked into human peripheral blood, the lower detection limit for RT-qPCR quantification of the bacteria was 2 cells per ml of blood, suggesting that this method was equivalent to the conventional culture method. As only 5 h was needed for RT-qPCR quantification, we suggest that rRNA-targeted RT-qPCR assays provide a sensitive and convenient system for quantification of commensal bacteria and for examining their possible invasion of a host.